Case Report: A neurodevelopmental disorder with global developmental delay, microcephaly, eye anomalies, sweat dysregulation, and skeletal implications due to an ultra-rare de novo 5q14.3q15 copy number gain - Serban, Costela Lacrimioara; Mihailescu, Alexandra; Miclea, Diana; Zimbru, Cristian G.; Stoica, Florina; Chirita-Emandi, Adela (Frontiers in Genetics, 2025)
This case report and literature review documents an ultra-rare de novo copy number gain at 5q14.3q15. The patient’s phenotype included hypotonia, microcephaly, global developmental delay, iris hypoplasia, atrophy, sweat dysregulation, and skeletal implications, including camptodactyly. This case presentation provides novel insights into the genotype–phenotype correlation for 5q14.3q15 copy number gain, particularly highlighting the involvement of the MEF2C gene (#MIM 600662). Through comprehensive clinical and genetic evaluation, we aim to enhance the understanding of this ultra-rare genetic condition and its implications.